Sistema web de gestión para la compra venta de bienes raíces de la federación interprovincial de centro shuar-ficsh. - Taisha Unkuch, Paúl Alexander (2019)
This research study was carried out at the ‘Federación Interprovincial de Centros Shuar’ (FICSH). It was identified that the Real Estate Purchase-Sale was carried out manually, which implied the loss of documents, procedures related to the sale were delayed, and disagreements were generated by users in the associated centers belonging to the FICSH. To develop this technological proposal, scientific articles were searched. These books and institutional documents allowed acquiring timely information on the background and tools that contributed to the development of the web system. The research methodology applied was a mixed approach, descriptive level. The applied design was carried out through bibliographic research and field research with the support of the observation technique, interview and surveys to collect data. The methodology used for the development of the web system was based on the Interactive Incremental methodology, the sublime tool Text as a code manager and MySQL for the development of the database. The system allows managing the processes of buying and selling real estates, among the main activities are managing authorities, managing associations, managing sales and generating the Real Estate Purchase-Sale contract. In conclusion, all the specified requirements were met, reaching the satisfaction of the user.